Editorial: Immunotherapy in renal cell carcinoma - Gruenwald, Viktor; Storkus, Walter J. (Frontiers in Oncology, 2022)
This collection contains 10 reports published In Frontiers in Oncology between August 2020 and March 2022 broadly focused on the immunobiology of renal cell carcinoma (RCC), the impact of immunotherapy in the setting of RCC, and the identification of biomarkers that are prognostic of RCC patient outcomes and response to immunotherapy.